Gendered nationality gendered nation: analyzing gender equality within the 2004 nationality law reform in Egypt - Baitelmal, Marwa Salem (AUC Knowledge Fountain, 2012)
Nationality law holds a particular political agenda; it has the ability to dictate our membership within a nation and our relationship with the state. Essentially, it is through nationality law that we are extended membership within the enlarged community of the nation. As such, the law carries with it the ability to create the insider while in turn creating the outsider. This distinction becomes blurred when negotiating belonging for women who fall within this gap of the internal/external divide. Women, when forced to negotiate with the nationality law, find themselves as partial members. Their nationality is of a conditional one, finding that their completion within a patriarchal hegemony is ultimately through a male counterpart, obstructing her ability to place herself at equal standing. Further, we see how law dictates a limited membership for women when their right to filiation and family unity is provisioned with the inclusion of a male member. This shows true in the case of women in Egypt, where nationality law has conditioned her membership as an unequal one. Therefore, at a moment in history where states are re-evaluating laws and reforming national membership, it is essential to examine the 2004 law reform in Egypt, which can serve as a litmus test towards understanding the limitations the reform has had in achieving equality for women. Therefore, by demonstrating its inability to achieve gender equality by realizing that the Egyptian woman’s membership is limited, and her rights to forming a family unit, the freedom to choose a marriage partner without the fear of excluding family members are provisional. As such, the aim here is to shed light on the 2004 reformed nationality law in Egypt which has drawn approving attention for its positive move towards gender equality. Instead, it is important to deconstruct the various aspects of the 2004 nationality law that will then demonstrate the continued disadvantage and inequality imposed upon the Egyptian woman despite the reform.